Neutrophil Lymphocyte Ratio of Ischemic Stroke Based on Region of Lesion - Tandiono, Michelle; Edison, Rizki Edmi; Suhartomi, Suhartomi (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Ischemic stroke is a type of stroke that occurs when blood arteries get blocked as a result of embolic or thrombotic events. Brain imaging tools, particularly CT Scans, are the gold standard for diagnosing stroke. Blood tests were also performed, focusing on neutrophils and lymphocytes in particular. The prognosis for stroke can be determined by the neutrophil lymphocyte ratio (NLR). However, based on CT Scan imaging, it is currently unknown how the NLR and brain region of ischemic stroke are related.  Purpose : This study investigates the correlation between  CT scan images in ischemic stroke patients with Neutrophil Lymphocyte Ratio (NLR).Methods: It is a cross-sectional design study with observational method, this study involved 36 patients that were selected based on inclusive and exclusive criteria. Data was collected from medical records in Royal Prima Hospital and analyzed with Mann-Whitney Test.Results: The result shows that CT scan images in ischemic stroke patients does not have a significant correlation to NLR, with p value > 0,05.Conclusion:This study reveals that there is no significant correlation between CT scan images in patients with ischemic stroke and NLR. There may be other factors that influence the NLR such as age, stress level, obesity and medication. Further research needs to be conducted to study those other factors.